Senior High School Program Graduates and Teachers’ Satisfaction and Challenges: Spring Board of Plan Adjustments - Trinidad, Edna D.; Sabacajan, Bazil T.; Morados, Alexander N.; Nahial, Wenie L. (Future Science / FSH-PH Publications, 2024)
The study was conducted to determine the challenges and satisfaction of the teachers and graduates on the implementation of Senior High School (SHS) Program. Out of 1615 first batch graduates of school year 2017-2018, 306 of them were used as respondents of this study. These respondents were enrolled in two colleges in the Province of Camiguin. While 91 out of 130 SHS teachers from 10 public schools in DepEd-Camiguin represented were used as sample from the SHS implementers. The study utilized the quantitative-descriptive method to answer the research questions. Frequency, mean, ANOVA and multiple regressions were used to analyse the data. The study revealed that the graduate respondents were very disappointed in schools with no laboratories and workshops. They had difficulties in demonstrating their knowledge into actual experiential learning for the tools, materials, equipment and updated audio-visual materials needed were not available, if there were, and then it is not enough. Also, students’ research activities were impeded for no internet connections and other instructional resources available for to use. On the other hand, SHS teachers needed more TGs and CGs, teaching supplies and materials, laboratories and workshops to be effective and efficient to support learning. The graduates were not satisfied on the teachers’ effectiveness and efficiency in delivering the lessons to them. The overall results revealed that there is no significant relationship between satisfactions and challenges among SHS graduates and teachers’ in SHS program implementation. This study found out the need to implement adjustment to address the challenges identified by the respondents. Various programs and activities were needed to address the shortages and needs of the Senior High School community. Moreover, the outcome of the plan adjustments is to encourage the optimistic response of the department heads, school heads, teachers and students. By so doing, improvements will be transpired.